A Field Key to the Developmental Stages of Marine Turtles (Cheloniidae) with Notes on the Development of Dermochelys - Miller, Jeffrey D.; Mortimer, Jeanne A.; Limpus, Colin J. (Chelonian conservation and biology, 2017)
Descriptions of the developmental stages of embryonic marine turtles are presented in the form of a dichotomous key supported by drawings to facilitate identifying stages of development in the field. The key emphasizes the sequential appearance or loss of external morphological structures that can be seen either with the unaided eye or with a ×10 hand lens and a handheld light. Stages are placed in the context of normal beach temperatures to facilitate estimation of laying date, emergence date, and events that cause embryonic mortality. Measurements of embryos are presented to assist determining stage.